Archaeology and the information age - Reilly, P (Routledge, 1992)
Traditional methods of making archaeological data available are becoming increasingly inadequate. Thanks to improved techniques for examining data from multiple viewpoints, archaeologists are now in a position to record different kinds of data, and to explore that data more fully than ever before. The growing availablility of computer networks and other technologies means that communication should become increasingly available to international archaeologists. Will this result in the democratisation of archaeological knowledge on a global basis? Contributors from Western and Eastern Europe, the Far East, Africa and the Americas seek to answer this and other questions about the way in which modern technology is revolutionising archaeological knowledge.